What Drives Innovation? : Lessons from COVID-19 R and D - Agarwal, Ruchir; Gaule, Patrick (Washington, D.C. : International Monetary Fund, 2021)
To examine the drivers of innovation, this paper studies the global R and D effort to fight the deadliest diseases and presents four results. We find: (1) global pharmaceutical R and D activity-measured by clinical trials-typically follows the 'law of diminishing effort': id est the elasticity of R and D effort with respect to market size is about 1\2 in the cross-section of diseases; (2) the R and D response to COVID-19 has been a major exception to this law, with the number of COVID-19 trials being 7 to 20 times greater than that implied by its market size; (3) the aggregate short-term elasticity of science and innovation can be very large, as demonstrated by aggregate flow of clinical trials increasing by 38% in 2020, with limited crowding out of trials for non-COVID diseases; and (4) public institutions and government-led incentives were a key driver of the COVID-19 R and D effort-with public research institutions accounting for 70 percent of all COVID-19 clinical trials globally and being 10 percentage points more likely to conduct a COVID-19 trial relative to private firms. Overall, while economists are naturally in favor of market size as a driving force for innovation (i.e.'if the market size is sufficiently large then innovation will happen'), our work suggests that scaling up global innovation may require a broader perspective on the drivers of innovation-including early-stage incentives, non-monetary incentives, and public institutions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: COVID-19; Innovation; Market Size; Pharmaceutical Industry